2017
DOI: 10.1007/s13205-017-0773-y
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-mediated biodegradation of long-chain n-alkanes (C32 and C40) by thermophilic bacteria

Abstract: Removal of long-chain hydrocarbons and nalkanes from oil-contaminated environments are mere important to reduce the ecological damages, while bioaugmentation is a very promising technology that requires highly efficient microbes. In present study, the efficiency of pure isolates, i.e., Geobacillus thermoparaffinivorans IR2, Geobacillus stearothermophillus IR4 and Bacillus licheniformis MN6 and mixed consortium on degradation of long-chain n-alkanes C 32 and C 40 was investigated by batch cultivation test. Biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…The accumulation of these products resulted in the induction of the activity of these degradative enzymes. Previous studies also showed that less lipase enzyme was induced during the early incubation period, followed by a rapid increase in enzyme production when the hydrocarbon content decreased (Margesin et al, 2000;Elumalai et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The accumulation of these products resulted in the induction of the activity of these degradative enzymes. Previous studies also showed that less lipase enzyme was induced during the early incubation period, followed by a rapid increase in enzyme production when the hydrocarbon content decreased (Margesin et al, 2000;Elumalai et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…Biodegradative enzymes present a significant role in microbial degradation of petroleum hydrocarbons (Yong and Zhong, 2010;Wasoh et al, 2019). The hydrocarbon removal efficiency depends on the bacteria used and their enzymatic oxidation characteristics (Elumalai et al, 2017). In the alkane degradation pathway, the degradation of n-alkane is usually initiated by alkane hydroxylase enzymes that transform alkane into alkanols by targeting different ranges of hydrocarbon (van Beilen et al, 1994;Singh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although short‐chain alkanes, naphthalene and 1‐methylnaphthalene were degraded in the first 6 days, an increase in their concentration was observed after 21 days. Since the biodegradation of complex compounds generates less complex intermediates (Elumalai et al ; Hou et al ), we hypothesized that this increase in concentration could be due to the accumulation of intermediates from the degradation of more complex aliphatic and aromatic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…For n-alkanes (C 8 -C 40 ), the aerobic degradation is divided into three oxidation modes [124]. These modes are known as terminal oxidation [125], subterminal oxidation [126], and biterminal oxidation [127]. The oxidation modes take place at different carbon positions and form various end products.…”
Section: Mechanisms Involved In Diesel Bioremediation By Bacteriamentioning
confidence: 99%